A study on the adverse effects of right wing populism on foreign policy - Tinwalla, Sasha Carlotta (2018)
This paper aims to understand the adverse effects of populism on a states' foreign policy particularly in democracies where radical right wing populist leaders have been elected. Populism is an ongoing phenomenon that is spreading through democracies. Undoubtedly, domestic politics affect foreign policy as they are interlinked. An ideal foreign policy pursues national interest in line with the common interests of the international society and does not disrupt the international system. By outlining that populist leaders utilise rhetoric that marginalises a distinct 'other' and pursue policies that are nationalistic for maintaining territorial sovereignty, there is a possibility that these could undermine the shared norms and reduce obligations towards international society. Case studies of Hungary, India, Philippines, and the United States of America will aid in demonstrating the implications an elected populist government can have on the state's foreign policy.